2022
DOI: 10.1002/ar.24956
|View full text |Cite
|
Sign up to set email alerts
|

Antler tine homologies and cervid systematics: A review of past and present controversies with special emphasis onElaphurus davidianus

Abstract: Antlers are the most conspicuous trait of cervids and have been used in the past to establish a classification of their fossil and living representatives. Since the availability of molecular data, morphological characters have generally become less important for phylogenetic reconstructions. In recent years, however, the appreciation of morphological characters has increased, and they are now more frequently used in addition to molecular data to reconstruct the evolutionary history of cervids. A persistent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…Recent phylogenetic analysis has revealed an ancestral divergence of the common ancestors of the Axis and Rucervus sp. groups from the main phylogenetic lineage of the tribe cervini, which later radiated in the genus Cervus, Rusa, Elaphurus and Eld's deer (Heckeberg et al 2022). Based on its ancestral divergence, Eld's deer is phylogenetically more closely related to the genus Cervus than to Rucervus, and the morphological similarities with R. duvaucelii and R. schomburgki characterize convergence rather than phylogenetic relatedness (Ghazi et al 2021).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phylogenetic analysis has revealed an ancestral divergence of the common ancestors of the Axis and Rucervus sp. groups from the main phylogenetic lineage of the tribe cervini, which later radiated in the genus Cervus, Rusa, Elaphurus and Eld's deer (Heckeberg et al 2022). Based on its ancestral divergence, Eld's deer is phylogenetically more closely related to the genus Cervus than to Rucervus, and the morphological similarities with R. duvaucelii and R. schomburgki characterize convergence rather than phylogenetic relatedness (Ghazi et al 2021).…”
Section: Taxonomymentioning
confidence: 99%
“…Analyses of mitochondrial data have placed Père David's deer (Elaphurus davidianus) as the sister taxon to Eld's deer (Heckeberg et al 2022). Recent studies, four based on genetics and another on antler morphology, have suggested that Eld's deer is actually more closely related to Père David's deer than to species of the genus Rucervus (Hassanin et al 2012;Turvey et al 2017;Heckeberg 2020;Samejima and Matsuoka 2020;Ghazi et al 2021).…”
Section: Taxonomymentioning
confidence: 99%